Txnip expression promotes JNK-mediated neuronal death in response to reactive oxygen species - García-Hernández, Brenda; Morán, Julio (Frontiers in Molecular Neuroscience, 2023)
TXNIP is a protein sensitive to oxidant conditions whose expression is related to the progression of death in cancer, diabetes, ischemia, and neurodegenerative diseases, among others. Because of this, many studies propose TXNIP as a therapeutic target in several diseases. Exposure of cerebellar granule neurons to staurosporine or low potassium leads to apoptotic death. Both conditions generate an early production of reactive oxygen species (ROS) that induces the activation of the ASK1 pathway and the apoptotic machinery. In these models, it has been shown an increase in TXNIP protein mediated by ROS. Here, we evaluated the molecular mechanisms involved in the regulation of the Txnip expression during neuronal death, as well as the role of the protein in the progression of cell death induced by these two apoptotic conditions. In cultured cerebellar granule neurons, we observed that low potassium and staurosporine induced an early increase in ROS that correlated with an increase in Txnip mRNA. When we evaluated the promoter of the gene, we found that the JASPAR-reported FOXO1/3 transcription factor motifs are close to the transcription start site (TSS). We then verified through the Chromatin immunoprecipitation technique (ChIP) that FOXO3 interacts with the Txnip promoter after 1 h of low potassium treatment. We also detected FOXO3 nuclear translocation by low potassium and staurosporine treatments. Finally, by using shRNA in the neuroblastoma MSN cell line, we found that Txnip downregulation decreased neuronal death induced by staurosporine stimulus. Together, these results suggest that ROS promote the expression of Txnip through the activation of the FOXO3 transcription factor mediated by Akt inhibition. We also demonstrated that TXNIP is necessary for neuronal death progression.